Longitudinal Multi-Channel Focused Vortex and Vector Beams Generation by Quarter-Wave Plate Meta-Atom Metasurfaces - Teng Ma; Kaixin Zhao; Manna Gu; Haoyan Zhou; Chunxiang Liu; Chuanfu Cheng; Qingrui Dong; Li Ma (Nanomaterials)
Metasurface-based longitudinal modulation introduces the propagation distance as a new degree of freedom, extending the light modulation with metasurfaces from 2D to 3D space. However, relevant longitudinal studies have been constrained to designing the metasurface of half-wave plate (HWP) meta-atoms and generating either non-focused or two-channel vortex and vector beams. In this study, we propose a metasurface composed of quarter-wave plate (QWP) meta-atoms to generate the longitudinal multi-channel focused vortex and vector beams. The metasurface consists of two interleaved sub-metasurfaces of QWP meta-atoms. For each sub-metasurface, the helical and hyperbolic phase profiles are designed independently in the propagation and geometric phases to generate focused co- and cross-polarized vortices with corresponding topological charges. Under the illumination of x-linearly polarized light, the metasurface generates two circularly polarized vortices, two linearly polarized vortices, and one vector beam on five focal planes. Theoretical analysis and simulation results demonstrate the feasibility of the proposed QWP metasurface. Our study presents a significant advancement in the development of integrated and multifunctional optical devices and systems, with significant potential applications in light–matter interaction, laser processing, and optical communication.